ANALISIS RENCANA PENGEMBANGAN USAHA TERMINAL PENUMPANG GIWANGAN (STUDI PADA TERMINAL PENUMPANG YOGYAKARTA) - ANIN, MATHEOS ADOLOF ([Yogyakarta] : Universitas Gadjah Mada, 2015)
This research is an implementation of business feasibility analysis toward developed business in Yogyakarta Passenger Terminal herewith TPY located in Giwangan. This research is purposed to conduct an analysis toward investment plan on Giwangan Passenger Terminal post-takeover of management right by city government of Yogyakarta as an effort of asset optimization and local revenue sources. Particularly, the assets of kiosks which are located in block A/B of TPY. The data analysis consists of primary and secondary data. The primary data includes rental revenue and expenditure data which are proposed as alternative use, obtained from structural interview and internet access, while the physical data is obtained from direct investigation. The secondary data is obtained from Company of Transportation Department and UPT TPY, Statistic Center Agency, and some working unit's area on Yogyakarta City Governmental. Based on the outcome of physical and regulation analysis are obtained two development alternatives. Alternative I is kiosk reparation/rehabilitation and parking lot expansion. Alternative II is new construction of kiosk building and parking lot expansion. Both alternatives are assumed with economic value during 20 years. The outcome of feasibility analysis indicates that both alternatives said to be feasibly accepted as profitable business using several methods such as Average of Return (ARR), Payback Period (PBP), Net Present Value (NPV), Internal Rate of Return (IRR) and Profitability Index (PI). Net Present (NP) projection of net cash in Alternative I is Rp 9.000.473.053, alternative II is Rp10.804.484.324, and TPY is Rp11.743.411.615. It means that, when one of alternative is not conducted, Local Own-source Revenue of Yogyakarta City will lost about Rp9.000.473.053 - Rp10.804.484.324 of NP-net cash within 20 years ahead. This research analyzed based on the physical, legal and financial aspect. Therefore, the further research needs to be conducted by considering several feasibility aspects, includes other forms of compatible business development for spatial planning and territory (RTRW). Keywords: Analysis of Business Feasibility, Investment Plan, Alternative I, Alternative II